GENERAL DESCRIPTION OF SEED FRUIT GARDEN AGROSENOSES OF WESTERN FERGANA - Kxomidova Zulxumor Mansurjonovna; Qodirova Gulyora Dehqonboy qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides a general description of the Western Fergana region, a description of the agrocenoses of the seed and fruit garden. The climatic conditions of the Western Fergana region are characterized by relatively dry and high temperatures during the season, and sometimes there is a large-scale increase of harmful insects and the formation of breeding centers in these regions.